Curative Effect of Wearable Back Trainer Combined with Massage on Patients of Chronic Nonspecific Low Back Pain - An CAO; Guozhi HUANG; Qing ZENG; Peichen HE; Rihui LI (康复学报)
Objective:To observe the clinical efficacy of the wearable back trainer combined with massage on chronic nonspecific low back pain patients.Methods:A total of 56 chronic nonspecific low back pain patients were randomly assigned to three groups. The treatment group (n=19) was treated with wearable device treatments based on massage for two weeks, once a day, eight minutes each time, five times a week, while the control group (n=19) received massage only for two weeks, once a day, 20 minutes each time, and the blank group (n=18) rest only with closely observation. The therapeutic effect of three groups were evaluated by VAS and ODI scores before the treatment, one week after treatment and two weeks after treatment respectively.Results:There was no statistical difference among the three groups in VAS score before treatment (P> 0.05). There were statistical differences among the three groups in VAS score one week after treatment and two weeks after treatment respectively (P< 0.05); the score showed a downward trend with time, the decreasing amplitude of VAS score in the treatment group was higher than that of control group two weeks after treatment (P< 0.05), and the decreasing amplitude of VAS score in the treatment group and the control group was higher respectively than that of blank group one week after treatment and two weeks after treatment (P< 0.05). There was no statistical difference among the three groups in ODI score before treatment and one week after treatment (P> 0.05). There were statistical differences among the three groups in ODI score two weeks after treatment respectively (P< 0.05); the score showed a downward trend with time in the treatment group and the control group, the decreasing amplitude of ODI score in the treatment group was higher than that of control group two weeks after treatment (P< 0.05), and the ODI value in the blank group was decreased one week after treatment and increased two weeks after treatment.Conclusion:The clinical efficacy of the wearable back trainer combined with massage has good effect on patients of chronic nonspecific low back pain, and the effect of the combined therapy is better than simple massage therapy especially in pain relief.